Clinical and Molecular Characterization of ALG1-CDG - Radhika Dhamija; Chelsea Chambers (Pediatric Neurology Briefs Publishers, 2016)
Investigators from the Human Genetics Program, Sanford Burnham Prebys Medical Discovery Institute, La Jolla, California and a large study group utilized a combination of exome sequencing, targeted gene panels, and Sanger sequencing to identify thirty-one pathogenic variants in thirty-nine affected individuals with ALG1-CDG from 32 families.